The Correlation Between the Implementation of Chemistry Learning and Student Learning Outcomes Using a Google Classroom-Based Blended Learning Model - Yunus, Muhammad; Islawati, Islawati; Febrianti, Nining; Sugiarti, Sugiarti (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to examine the correlation between the implementation of Chemistry learning and student learning outcomes through a Google Classroom-based Blended Learning model. This research is a type of descriptive quantitative study. Data were collected in the form of the implementation of learning and student learning outcomes, which were then analyzed using the Pearson correlation test. The observations showed that the implementation of learning reached 100% for both pre- and post-online learning sessions, and 86% for face-to-face learning. The average score of student learning outcomes in the experimental group was 80.25 with a standard deviation of 10.65. The analysis revealed a very strong and significant correlation between the implementation of learning and student learning outcomes, with a correlation value (r) of 0.957, indicating that the higher the implementation of learning, the better the student learning outcomes. This indicates that the use of the Google Classroom platform in the Blended Learning model contributes significantly to improving student learning outcomes.